Edukasi Seksual Bagi Remaja Kebupaten Brebes - Suci Fitriana Pramudya Wardani; Fristiyanti, Regina Ayu; Permatasari, Ineke; Aimang, Irna Olvaliani; Tafuli, Yordayumike; Santi, Ida Ayu Made Ari (Jurnal Pengabdian Bidang Kesehatan, 2026)
Sexual education plays a critical role in promoting healthy and responsible behaviors among adolescents. Insufficient knowledge about sexual health increases the risk of engaging in unsafe sexual practices. This study aimed to evaluate the effectiveness of sexual education in improving the knowledge of students at SMP Pancasila, Brebes Regency, regarding adolescent sexual issues. The intervention was conducted in May 2024 with 24 students aged 12–18 years, using a pretest-posttest design and educational media, including leaflets and PowerPoint presentations. Results indicated a significant increase in the average knowledge score from 7 to 9 following the intervention. Most participants were aged 14–17 years, and some had prior dating experience. These findings are consistent with Erikson’s developmental theory, highlighting the importance of identity formation and intimacy during adolescence. The educational program effectively enhanced students’ knowledge and equipped them with decision-making skills, self-regulation, and body awareness. This study underscores the necessity of implementing comprehensive sexual education at the middle school level, involving schools, parents, and the community, and employing accurate educational materials such as leaflets. Such interventions are expected to reduce the incidence of premarital sexual behavior and foster responsible attitudes among adolescents